Thymoquinone Inhibits Proliferation and Migration of MDA-MB-231 Triple Negative Breast Cancer Cells by Suppressing Autophagy, Beclin-1 and LC3 - Ünal, Tuba D.; Hamurcu, Zuhal; Delibaşı, Nesrin; Çınar, Venhar; Güler, Ahsen; Gökçe, Sevda; Nurdinov, Nursultan; Ozpolat, Bulent (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Triple Negative Breast Cancer (TNBC) is an aggressive and highly heterogeneous subtype of breast cancer associated with poor prognosis. A better understanding of the biology of this complex cancer is needed to develop novel therapeutic strategies for the improvement of patient survival. We have previously demonstrated that Thymoquinone (TQ), the major phenolic compound found in Nigella sativa, induces anti-proliferative and anti-metastatic effects and inhibits in vivo tumor growth in orthotopic TNBC models in mice. Also, we have previously shown that Beclin-1 and LC3 autophagy genes contributes to TNBC cell proliferation, migration and invasion, suggesting that Beclin-1 and LC3 genes provide proto-oncogenic effects in TNBC. However, the role of Beclin-1 and LC3 in mediating TQ-induced anti-tumor effects in TNBC is not known. Objective: To investigate the effects of TQ on the major autophagy mediators, Beclin-1 and LC3 expression, as well as autophagic activity in TNBC cells. Methods: Cell proliferation, colony formation, migration and autophagy activity were evaluated using MTS cell viability, colony formation assay, wound healing and acridine orange staining assays, respectively. Western blotting and RT-PCR assays were used to investigate LC3 and Beclin-1 protein and gene expressions, respectively, in MDA-MB-231 TNBC cells in response to TQ treatments. Results: TQ treatment significantly inhibited cell proliferation, colony formation, migration and autophagic activity of MDA-MB-231 cells and suppressed LC3 and Beclin-1 expressions. Furthermore, TQ treatment led to the inhibition of Integrin-β1, VEGF, MMP-2 and MMP-9 in TNBC cells. Conclusion: TQ inhibits autophagic activity and expression of Beclin-1 and LC3 in TNBC cells and suppresses pathways related to cell migration/invasion and angiogenesis, including Integrin-β1, VEGF, MMP-2 and MMP- 9, suggesting that TQ may be used to control autophagic activity and oncogenic signaling in TNBC.
Keywords: MMP-9